2017
DOI: 10.1080/13501763.2017.1298658
|View full text |Cite
|
Sign up to set email alerts
|

Public opinion on policy and budgetary trade-offs in European welfare states: evidence from a new comparative survey

Abstract: In the wake of the 'Great Recession', welfare states have entered a new phase of austerity. Simultaneously, new social risks and the rise of the knowledge economy fuel new demands on the welfare state. We analyse how demands for social investment policiesparticularly educationcome into conflict with budgetary concerns, using new survey data on individual-level preferences in eight European countries. Paying particular attention to fiscal and budgetary trade-offs, we find that social investments are generally v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(62 citation statements)
references
References 32 publications
2
55
1
4
Order By: Relevance
“…Are respondents willing to pay for their preferred level of welfare state spending or do they engage in trade-offs when forming their welfare state and redistribution preferences? Following up on a long-standing, but sometimes neglected, line of public opinion research [7,17,18] and contributing to recent trends in welfare state research [14,23,33], we have shown that tax constraints lead to lower aggregate support for the welfare state. But our results clearly show that such trade-offs between spending and taxes do not apply to all areas of the welfare state and might only be relevant for policies that provide concentrated benefits for some people, such as unemployment benefits or redistribution, social investment [14], or family policy [8].…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…Are respondents willing to pay for their preferred level of welfare state spending or do they engage in trade-offs when forming their welfare state and redistribution preferences? Following up on a long-standing, but sometimes neglected, line of public opinion research [7,17,18] and contributing to recent trends in welfare state research [14,23,33], we have shown that tax constraints lead to lower aggregate support for the welfare state. But our results clearly show that such trade-offs between spending and taxes do not apply to all areas of the welfare state and might only be relevant for policies that provide concentrated benefits for some people, such as unemployment benefits or redistribution, social investment [14], or family policy [8].…”
Section: Discussionmentioning
confidence: 77%
“…One problem which arises here is that explicitly adding one constraint or trade-off-in our case, between additional spending and taxes-might encourage respondents to think also about other possible trade-offs. Increasing deficits or cutting other welfare state programs are two other alternatives to finance more spending [14,17]. Also, adding a tax constraint raises awareness that someone has to pay for the additional spending, but it remains open to the respondents' interpretation of who should pay [23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations